PERANCANGAN DASHBOARD PENJUALAN UNTUK FAMILY MAKATI CENTER - Chelsen (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Family Makati Center (FMC) is a branch of the HDI company in the Philippines. The HDI firm sells these beekeeping supplies separately. These products include supplements, personal care products and skin care that have undergone clinical trials and have health certificates from various relevant organizations. The goal of this thesis is to create a dashboard that displays a visualization of sales data. The data utilized is from the proprietor of the Family Makati Center (FMC) from August 2021 to August 2022. Prototyping is used in the dashboard design. The displayed data may then help businesses uncover specifics and comprehensive information about sales in a chart or graphic presentation. The end result of this design is a sales information reporting dashboard that allows owners to observe the progress of items sold each month and correctly regulate sales transactions.